Entre archive et pratiques vivantes - Jean-Jacques Castéret (Ateliers d'Anthropologie)
Since the mid-2000s, the current Centre international de recherche et documentation occitanes – Institut occitan de cultura (labelled Ethnopôle by the Ministry of Culture) has been working on accessibility to oral archive collections as well as on the inventory and promotion of immaterial cultural heritage through online publication. The past fifteen years have seen the appearance of various thematic websites and web portals, mediation tools gradually building a digital ecosystem that also includes social networks. This article reviews the documentary, technological, territorial and political logic underpinning the centre’s action at the intersection of research and cultural mediation, between archives and living practices; inventory and education in art and culture; appropriation of resources by artists and actors in the field.